2017
DOI: 10.5753/rbie.2017.25.02.87
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura Ontológica para representar Papéis Colaborativos Afetivos em ambientes CSCL

Abstract: Resumo O uso de ontologias para representar os cenários CSCL tem sido investigado por diversos pesquisadores na literatura. Apesar das importantes contribuições desses trabalhos, observou-se a carência de estudos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
1
5
0
5
Order By: Relevance
“…The Group Recommender system used a KNN (K-Nearest Neighbors) data mining algorithm to suggest learners with similar personality traits. Reis et al (2018) extended the previous review and found three other studies Iima, 2008, 2009;Farhangian et al 2015) to support group formation based on prediction models. Iima (2008, 2009) observed the use of neural networks and genetic algorithms for the prediction of learning results in group work, based on their personality trait.…”
Section: Related Worksupporting
confidence: 69%
See 4 more Smart Citations
“…The Group Recommender system used a KNN (K-Nearest Neighbors) data mining algorithm to suggest learners with similar personality traits. Reis et al (2018) extended the previous review and found three other studies Iima, 2008, 2009;Farhangian et al 2015) to support group formation based on prediction models. Iima (2008, 2009) observed the use of neural networks and genetic algorithms for the prediction of learning results in group work, based on their personality trait.…”
Section: Related Worksupporting
confidence: 69%
“…Other examples of ACL roles can be found in the study developed by Reis et al (2016Reis et al ( , 2017. In Reis et al (2016) the ACL roles were based on a combination between introvert/extrovert personality traits and Anchored instructor/Problem holder CL roles, based on Anchored Instructor CL theory (CTGV, 1992).…”
Section: Affective Collaborative Learning Rolementioning
confidence: 99%
See 3 more Smart Citations